140 RISK ASSESSMENT OF STABLE CHEST PAIN PATIENTS AS PER NICE GUIDELINES FROM A RAPID ACCESS CHEST PAIN CLINIC CORRELATING ESTIMATED RISK OF CORONARY ARTERY DISEASE AND OUTCOMES BY ANGIOGRAPHY. (24th May 2013) - Murray, I P; Anderson, S; Cubukcu, A A
Abstract : Introduction: Patients presenting with symptoms suggestive of stable angina are routinely referred by their GP to a Rapid Access Chest Pain Clinic (RACPC) to assess whether there may be underlying coronary artery disease (CAD) which requires further investigation. NICE guidelines for the management of Stable Chest Pain of Recent Onset present an algorithm for the treatment of these patients. These guidelines have been implemented to various degrees in many NHS trusts, however there effectiveness has yet to be proved. A retrospective study was undertaken to assess the impact and relevance of the 2010 NICE guidelines by comparing the estimated risk of CAD with the angiographic findings. Method: 423 patients who attended the RACPC at Macclesfield District General Hospital (MDGH) between Jan-Dec 2011 were retrospectively studied (table 1 ). A Specialist Cardiology Nurse recorded a clinical history and risk assessed according to NICE guidelines dependent on whether their chest pain (CP) sounded non-anginal, atypical or typical for angina. If appropriate an exercise tolerance test(ETT) was carried out. Dependant upon the typicality of symptoms, NICE estimated risk of CAD and ETT result patients were referred for further tests- stress echocardiography(SE) or angiography. By recording the outcomes of angiography we were able to compare the estimated risk of CAD to the actual prevalence of disease within the individual classifications. Results: Non-Anginal chest pain: 97% were successfully discharged after attending RACPC. No evidence of CAD was found in the 3% who underwent further investigation. Atypical angina: 32% were discharged, 11% referred for SE and 42% sent for angiogram. Only 35% of angiograms showed evidence of CAD with 17% sent on for revascularisation. Typical angina: 15% were discharged, 10% were referred for SE whilst 70% had an angiogram. Of these 56% were found to have evidence of CAD and 37% required revascularisation. Discussion: RACPC is an important service for screening patients with CP. Reassuringly most patients with non-anginal sounding CP were discharged without further testing and those which had further tests were clear of CAD. In patients with atypical or typical sounding angina, there appears to be an over reliance on angiography. 65% of atypical patients and 44% of typical patients had an angiogram with unobstructed arteries. Angiograms were performed in line with NICE guidance, that risk >61% should be sent for angiogram or treated as stable angina, but the results show an over-reliance on this invasive test. If NICE were to make better use of functional imaging, such as SE, some patients may be spared an invasive and risky procedure. Conclusions: RACPC provides an important service to help risk stratify patients with suspected stable angina. However use of NICE guidance with these patients appears to overestimate risk of CAD causing unnecessary referrals for angiography.